2013
DOI: 10.3892/ijo.2013.2025
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of case-control studies on acoustic neuroma diagnosed 1997–2003 and 2007–2009 and use of mobile and cordless phones

Abstract: We previously conducted a case-control study of acoustic neuroma. Subjects of both genders aged 20–80 years, diagnosed during 1997–2003 in parts of Sweden, were included, and the results were published. We have since made a further study for the time period 2007–2009 including both men and women aged 18–75 years selected from throughout the country. These new results for acoustic neuroma have not been published to date. Similar methods were used for both study periods. In each, one population-based control, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 23 publications
3
40
0
1
Order By: Relevance
“…Since then, a number of studies have been published of experimental results showing that radiofrequency fields affect cellular repair and increase biomarkers associated with cancer risk. in our view these results and several epidemiology studies (8,21) are consistent with what is expected if radiofrequency fields from mobile phone use are a cause of brain cancer: the higher the cumulative hours of use, the higher the risk; the longer the time since first use, the higher the risk; the higher the radiated power, the higher the risk; ipsilateral risk is higher than contralateral risk.…”
Section: Glioma Meningioma ------------------------------------------supporting
confidence: 79%
See 4 more Smart Citations
“…Since then, a number of studies have been published of experimental results showing that radiofrequency fields affect cellular repair and increase biomarkers associated with cancer risk. in our view these results and several epidemiology studies (8,21) are consistent with what is expected if radiofrequency fields from mobile phone use are a cause of brain cancer: the higher the cumulative hours of use, the higher the risk; the longer the time since first use, the higher the risk; the higher the radiated power, the higher the risk; ipsilateral risk is higher than contralateral risk.…”
Section: Glioma Meningioma ------------------------------------------supporting
confidence: 79%
“…Of particular interest are studies from Sweden and Korea. In the Korean study, significant increases for acoustic neuroma occurred with >2,000 cumulative hours of use when compared to less (7), and in the Swedish study for >2,300 h of cumulative use (8). In three studies, increased risks for meningioma were also found at the highest cumulative hours of use (5,6,9).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations